Milo stover, forage sorghum, prairie hay, soybean meal and urea compared for growing heifers - Bolsen, K.; Oltjen, J.; Ilg, H. (Kansas State University. Agricultural Experiment Station, 2011)
Milo stover silage, prairie hay or forage sorghum silage was fed in rations containing 10, 12 or 14% protein from soybean meal (SBM) or 12% protein from urea; 100 heifers were fed in the 78-day growing trial (November 11, 1977 to February 2, 1978). Heifers fed forage sorghum silage, prairie hay or forage sorghum silage + prairie hay had similar rate and efficiency of gains; those fed milo stover silage made slowest and least efficient gains. Rations containing prairie hay were consumed in the greatest amounts. Feeding rations with 12 or 14% protein from SBM gave better performance than rations with 10% protein from SBM. Heifers fed urea gained slower and less efficiently than those fed SBM. Gain from a ration containing equal parts of milo stover silage and forage sorghum silage exceeded predicted gain by 7.8%, and efficiency was 13.9% better than predicted.
Keywords: Beef; Milo stover; Forage sorghum; Prairie hay; Soybean meal; Urea; Heifers